Potable Water Supply Feasibility Study for Summit Station, Greenland - Haehnel, Robert B.; Knuth, Margaret A. (2011)
This study reviews potable water production methods that may be applicable for use at Summit Station, Greenland. The two methods that are most widely used at polar field sites are melting surface snow and melting subsurface ice to form a well. There are limited published data on the energy usage for melting surface snow. Based on the data obtained from operations at Summit we determined that the basic energy requirement to melt the snow is about 2300 Btu/gal. This method, as currently implemented at Summit, is also a labor-intensive activity; there are opportunities to reduce the labor in this process with a new design of the system. The feasibility of using a subsurface well established in the glacial ice (Rodwell) at Summit was also analyzed. The approximate sustained energy requirement for this would be 30-40,000 Btu/hr, with an initial requirement of 142,000 Btu/hr for start-up. This feasibility study shows that a Rodwell can provide at least 10 years of service before it will need to be relocated. The specific energy requirement for this system ranges from 4100-7000 Btu/gal. or 1.8 to 3.0 times higher than the current system of melting surface snow. This study also shows that the Rodwell is more energy efficient when it is designed to supply more water to support a large population. The original document contains color images.